India’s economic reforms and challenges for industrialisation - Kalim Siddiqui (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
This study focuses on the issue of economic reforms and its impact on industrialisation in India. However, to understand this, it seems also crucial to analyse pre-economic reforms. In India, due to the prevalence of high unemployment and overburdened agriculture sector, the manufacturing sector becomes very important not only just in creating employment but also to boost manufacturing exports. The article examines existing literature on industrial sector in India and try to explain the challenges, it is currently facing. The 1991 economic reforms in India, removed tariff barriers to foreign investments and trade, with a hope that it will encourage foreign investors and ease burden on current accounts. The public sector and the role of the state in the economy was reduced and bureaucratic controls were dismantled, while at the same time the increasing the role of the market and private sector within the economy was strengthened. As a result, foreign capital investment and foreign exchange reserves improved. The study concludes that more than a quarter of a century has passed since pro-market policies were enacted, but such polices did not lead to rapid creation of employment opportunities. There has been no rapid growth of manufacturing sector and there has been no corresponding decline in the share in agricultural employment. Even the much heralded IT sector’s dramatic expansion over the last two decades has provided jobs directly to less than a million people.